1998
DOI: 10.1016/s0735-1097(97)00495-6
|View full text |Cite
|
Sign up to set email alerts
|

High Dose Bolus Heparin as Initial Therapy Before Primary Angioplasty for Acute Myocardial Infarction: Results of the Heparin in Early Patency (HEAP) Pilot Study

Abstract: Early therapy with high dose heparin is associated with full coronary reperfusion in a considerable number of patients with acute myocardial infarction, especially in those treated early (< 2 h). This simple, inexpensive, probably safe and easily antagonizable treatment may be an attractive first treatment of acute myocardial infarction both before and during the hospital stay in conjunction with primary angioplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 16 publications
2
22
0
Order By: Relevance
“…15 In this study, it is observed that 0-1 TIMI flow before intervention obviously in case group was more than control group (99% versus 91.6%) but after intervention there was no significant difference between two groups (3% versus 1.1%). This expresses that the influence of primary PCI in treatment of STEMI patients and improvement of their clinical situation while heparin injection before PCI doesn't effect on the treatment.…”
Section: Vd 2--3 Vdmentioning
confidence: 52%
“…15 In this study, it is observed that 0-1 TIMI flow before intervention obviously in case group was more than control group (99% versus 91.6%) but after intervention there was no significant difference between two groups (3% versus 1.1%). This expresses that the influence of primary PCI in treatment of STEMI patients and improvement of their clinical situation while heparin injection before PCI doesn't effect on the treatment.…”
Section: Vd 2--3 Vdmentioning
confidence: 52%
“…[7][8][9][10] Of these 3 patients, 2 who had been treated with abciximab experienced profuse bleeding in the oral cavity or at a tracheostomy site, and both required a massive blood transfusion after PCI, but finally succumbed to hypovolemic shock. The other patient, who had not been treated with abciximab, developed retroperitoneal hematoma and recovered from transient hypovolemic shock after a blood transfusion.…”
Section: Bleeding Complicationsmentioning
confidence: 99%
“…5,6 However, the role of adjunctive heparin in patients treated with primary PCI is not well established, with the few previous studies showing variable results. [7][8][9][10] Therefore, we investigated the effect of the early administration of heparin in the emergency room (ER) on both initial infarct-related artery (IRA) patency and clinical outcome in patients with STEMI treated by primary PCI.…”
mentioning
confidence: 99%
“…One study shows that an intravenous bolus of high-dose heparin administered in the emergency room improves TIMI flow before primary PCI. 25) In practice, we usually administer heparin and antiplatelet agents immediately after diagnosing AMI in the emergency room. As a result, the proportion of patients with TIMI 0 flow at initial CAG decreased to about 60% in both groups.…”
Section: Duration Of Reperfusion Therapymentioning
confidence: 99%